A companion to twentieth-century poetry - Roberts, Neil (Blackwell companions to literature and culture, 2001)
Brings together 48 fresh and original contributions from practicing poets and leading scholars, who together offer critical and contextual coverage of the full range of English-language poetry in the last century. Brings together original contributions by leading international scholars and practising poets. Offers critical and contextual coverage of the full range of English-language poetry in the twentieth-century. Incorporates new readings of key selected texts. Embraces the extraordinary development of poetry over the century in twenty English-speakin
Keywords: English poetry : 20th century : History and criticism; American poetry : 20th century : History and criticism; English-speaking countries : Intellectual life : 20th century